Human Rights In The Case Of The Cage In The House Of The Non-Active Regent Of Langat Based On The Decision Of The Stabat District Court Number 555/2023/PN STB - Riskyka, Riskyka; Abdul Halim Nasution; Alisya Aprilya Dharmayani; Tria Adhelia; Azhahira Hafiza Amir; Amanda Pramudita; Ahmad Parlindungan (Fox Justi : Jurnal Ilmu Hukum, 2025)
Rights​ Man related case found cage man or prison man at home regent inactive in Langkat based on Decision Stabat District Court Number 555/2023/ (HAM) PN Stb question Serious about violation right basic human rights , torture and modern slavery , including a number of big victims who experienced treatment No humane in facilities that are not adequate . Research objectives This is analyze human rights violations that occurred in case this and the implementation law criminal in respond to human rights violations . Research use approach descriptive qualitative and type research used​ is library research . This method use study as well as data collection through studies used libraries​ is existing ingredients​ the relation with title , where the ingredients we get through books , legislation , articles , and so on . Focus study This is on the rights victim basis , protection state law , and analysis response judicial to action public . This study also examines not quite enough answer law perpetrator , good from aspect law criminal and also the rights of victims that must be protected as much as possible perhaps by the state. Findings show that although there is effort law in the form of decision Supreme Court , however Still Lots gap in implementation protection right basic man in system Indonesian law that is needed overcome , especially in context implementation harsh sanctions​ to human rights violators in the sector government area . This study give recommendation important to government and institutions justice For strengthen enforcement law and improve protection right basic humans in Indonesia.